Application of the concept of beneficial ownership in sukūk structures: 105 an Islamic legal analysis - Engku Ali, Engku Rabiah Adawiah; Klopic, Nermin; Ellias, Muhammad Ramadhan Fitri; Haron, Muhamad Nasir (International Shari'ah Research Academy for Islamic Finance (ISRA), 2015)
Asset ownership is an important aspect of ṣukūk structuring and issuance. However, a recurring and contentious issue regarding the underlying ṣukūk asset is the actual nature of its ownership and the corresponding legal implications for ṣukūk holders and other parties in the ṣukūk transaction. Many ṣukūk are based solely on beneficial ownership of the assets whilst legal title is retained by the originator or trustee. This paper attempts to ascertain the status of beneficial ownership vis-à-vis registered legal title from the Islamic legal perspective. The paper begins with an examination of the meaning, origin and status of beneficial ownership under English law. This is followed by a brief discussion on ownership (milkiyyah) from the Sharīʿah (Islamic law) perspective and a deliberation on the status of beneficial ownership under the Sharīʿah. Finally, the paper analyses the use of beneficial ownership in ṣukūk structures and its implication on ṣukūk holders and other parties in the ṣukūk transaction.